1958
DOI: 10.1139/o58-082
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolism of Animal Tissues Cultivated in Vitro: Iii. Amino Acid Metabolism of Strain L Cells in Completely Synthetic Media

Abstract: Strain L cells, of mouse fibroblastic origin, have been cultivated in vitro in completely synthetic medium M 150 and in various modifications of this medium. The amino acid changes in the nutrient medium during cell cultivation have been studied by paper chromatography. A characteristic pattern of amino acid uptake and accumulation in the medium has been found. No change in the alanine concentration was observed but omission of alanine from the culture medium resulted in its accumulation in appreciable amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1961
1961
1978
1978

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…According to our results the L strain cells in medium 199 plus 2% horse serum metabolized the amino acids somewhat differently than when maintained in a completely defined medium (Pasieka et al, 1958b). On the other hand, perhaps our results can be explained on the basis of observations of Pasieka et al that no amino acids accumulated when glutamine was omitted from the medium.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…According to our results the L strain cells in medium 199 plus 2% horse serum metabolized the amino acids somewhat differently than when maintained in a completely defined medium (Pasieka et al, 1958b). On the other hand, perhaps our results can be explained on the basis of observations of Pasieka et al that no amino acids accumulated when glutamine was omitted from the medium.…”
Section: Discussionsupporting
confidence: 54%
“…Information on the amino acid metabolism of cell cultures has been summarized recently by Morgan (1958), Eagle (1959), and Lucy (1960). With regard to the L strain of fibroblasts the cells of clone 929 take up some amino acids and accumulate others during maintenance in a defined medium (last two columns in Table 8, from Pasieka, Morton, and Morgan, 1958b). According to Sinclair (1960), this strain in a completely defined medium (Waymouth's) showed a rapid uptake of glutamine and accumulation of glutamic acid; ammonia also accumulated, even in the cell-free incubated medium.…”
Section: Discussionmentioning
confidence: 99%
“…xagler. ) Laboratory of Hygiene, Department of Il'ational Health and Welfare, Ottawa, Canada. Paper chromatographic studies on the amino acid metabolism of animal tissues in vitro (1) have shown that marked changes in amino acid content of synthetic medium JI 1 50 ( 2.3 ) occur during the cultivation period.…”
Section: Specific Determination Of Hydroxy-l-proline In Biological Mamentioning
confidence: 99%
“…Full details of the chromatographic procedures have been reported previously ( 1,9,10). Chick embryo extract was prepared by grinding 11-*The cooperation of Mr. C. E. Kerr, of this Department, in making the photographic preparations, is gratefully acknowledged.…”
Section: Specific Determination Of Hydroxy-l-proline In Biological Mamentioning
confidence: 99%